The effect of sucrose concentrations and different types of tube cap on in vitro growth of Dahlia (Dahlia sp.) using vermiculite as substrate - Rudiyanto Rudiyanto; Betalini Widhi Hapsari; Deritha Ellfy Rantau; Tri Muji Ermayanti (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.